2021
DOI: 10.18267/j.cebr.273
|View full text |Cite
|
Sign up to set email alerts
|

State-Business Relations from the Perspective of the Companies' Preparedness for the Changes Related to the Implementation of the Industry 4.0 Elements: A Case of the Czech Republic

Abstract: The purpose of this study is to investigate the expectations of the management of different industries in the Czech Republic related to governmental support for their implementation of Industry 4.0 and their preparedness for the challenges associated with these technological changes. Mixed research, specifically exploratory sequential design, was used. The findings of qualitative data analyses from in-depth semi-structured interviews (n=41) with representatives of different industry sectors formed subsequent q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 30 publications
1
4
0
Order By: Relevance
“…Jobs related to cybersecurity and IT were not mentioned at all by the respondents, which supports the previous findings of this paper related to IT skills and corresponds with the authors' previous paper, in which cybersecurity was not perceived as one of the threats related to the implementation of Industry 4.0, and only one-fifth of the respondents stated that some elements of cybersecurity were implemented internally (Olšanová et al, 2021).…”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…Jobs related to cybersecurity and IT were not mentioned at all by the respondents, which supports the previous findings of this paper related to IT skills and corresponds with the authors' previous paper, in which cybersecurity was not perceived as one of the threats related to the implementation of Industry 4.0, and only one-fifth of the respondents stated that some elements of cybersecurity were implemented internally (Olšanová et al, 2021).…”
Section: Resultssupporting
confidence: 90%
“…"Continual interdisciplinary learning and cooperation" indicates a lack of skills in narrow specializations further enhanced by low motivation for continuous learning, which leads to potential implications for the current education system in terms of a greater emphasis on building awareness of the importance of lifelong learning and it structural development based on industry needs. This was also indicated by the authors' previous research (Olšanová et al, 2021), suggesting that the adaptability of personnel to new conditions should not be overlooked, as it represents a serious concern for all companies, regardless of size. The most frequent keywords are openness to learn, learning, multidisciplinary, willingness to learn, and change.…”
Section: Resultsmentioning
confidence: 58%
See 1 more Smart Citation
“…Regarding Czechia, Krajčík (2021) ex amined the digitalization of SMEs and found a slow transition, lack of strategy, and lack of funds. Olšanová et al (2021) revealed that most large Czech companies have already imple mented Industry 4.0 elements and the critical threat is a lack of skilled labor. Managers ex pect some state incentives.…”
Section: Theoretical and Literature Reviewmentioning
confidence: 99%
“…(Wightman et al, 2023). The term comes from Germany, and its first use dates back to 2011 (Olšanová et al, 2021). Today, however, it is spread worldwide and offers many opportunities for developing businesses and the entire state or individual regions (Soukupová et al, 2020).…”
Section: Introductionmentioning
confidence: 99%